Influence of Organization Behavior Faultliness on the Organisational Performance Tour Operator’s Firms in Tanzania - Chindengwike, James Daniel (The Journal of Accounting and Management, 2025)
Organizational performance is critical to a company’s long-term success. The study attempted to examine the influence of organization behavior faultliness on the organizational performance tourism enterprises in Tanzania. Specifically, this study determines the influence of values on the organizational performance tour operator’s firms in Tanzania and study determine the influence of norms on the organizational performance tour operator’s firms in Tanzania. The population of study comprised of tour operator’s firms, where, the sample size was 107. The study used a cross sectional survey study design and employed mixed approach. Data from employee who have no administrative roles were collected using questionnaire, while interviews were used to collect data from employees who hold administrative positions. Quantitative data were analyzed using descriptive statistics and multiple linear regression model, whereby; qualitative data were analyzed using content analysis. The study observed that organization behavior faultliness influences organizational performance in tour operator’s firms in Tanzania. The study concluded that organization behavior faultliness has statistically significance to the organizational performance in tour operator’s firms in Tanzania. Thus, the study recommends that, the management of tourism tour operator’s firms should take careful to measures the organization performance in aspect of organization behavior faultliness influences.